Evaluation of Patient's Perceptions, Healing, and Reattachment After Conventional and Diode Laser Frenectomy: A Three-Arm Randomized Clinical Trial - ÖZTÜRK ÖZENER, HAFİZE; KURU, LEYLA (MARY ANN LIEBERT, INC, 2020)
Objective:The aim of this study is to compare the conventional and diode laser techniques in terms of patient's perceptions, epithelization, reattachment, and periodontal clinical parameters in the treatment of abnormal papillary frenum. Materials and methods:Forty-eight patients with abnormal papillary frenum were enrolled in the study. Patients were randomly assigned into three groups; conventional frenectomy operation (C group), diode laser-assisted frenectomy (L group), and diode laser-assisted frenectomy with conventional horizontal incision on the periosteum (L + P group). Post-operative pain, discomfort in speaking, and chewing scores were assessed with visual analogue scale (VAS) at post-operative 3rd hour and on days 1, 7, 14, 21, and 45. Epithelialization process of the wound surface was evaluated by hydrogen peroxide solution applied to the wound on days 7, 14, 21, and 45 following operations. The distance between the frenum attachment point and mucogingival junction (FMGJ) was recorded at baseline, post-operative 45th day, and 6th month to assess the reattachment of the frenum. Plaque index, gingival index, bleeding on probing, and probing depth were recorded at baseline and post-operative 7th, 14th, 21(st), and 45th days. Results:On the 1st and 7th day after operation, VAS pain score in the C group was significantly higher than in the L and L + P groups (p < 0.017). Difficulty in speaking and chewing scores were significantly lower in the L and L + P groups compared to the C group at post-operative 3rd hour and 7th day (p < 0.017). The FMGJ and epithelization period demonstrated no difference among the groups at any time point (p > 0.05). Conclusions:Our results suggest that diode laser provides better post-operative patient's perceptions than the conventional technique in frenectomy operation. In addition, both conventional and laser-assisted frenectomy surgeries prevent the frenum reattachment regardless of periosteal horizontal incision.
Keywords: labial frenum; lasers; laser therapy; visual analogue scale; post-operative pain; ND-YAG LASER; CARBON-DIOXIDE LASER; PULSED NDYAG LASER; PERIODONTAL TREATMENT; CO2-LASER; OPERATIONS; DIASTEMA; ADJUNCT; ER